Implementation of Reciprocal Teaching Learning Strategies for Teaching Nahwu - Atyatul Fidlya; Mu Ida Nur Fadilah; Nuril Mufidah (Arabiyyatī: Journal of Arabic Language Education, 2025)
This study delineates the design and implementation of the reciprocal teaching-learning strategy within a Nahwu Science curriculum and subsequently examines student perceptions of this pedagogical intervention. Employing a descriptive qualitative methodology, the research focused on a cohort of nineteen fourth-semester students enrolled in the Arabic Language Education Study Program (Class B) during the 2024 academic year. Data were gathered through systematic observation of instructional sessions, in-depth interviews with participants, and the collection of learning artifacts and documentation. The findings indicate that the reciprocal teaching strategy constitutes a viable pedagogical approach for Nahwu instruction. Its efficacy is attributed to a framework that actively engages students in the learning process, fostering independent and collaborative comprehension of the material, facilitating a deeper conceptual grasp through structured discussion and questioning, and culminating in the demonstration of acquired knowledge via assessed assignments.